2016
DOI: 10.1177/1477750916657666
|View full text |Cite
|
Sign up to set email alerts
|

Empirical and philosophical analysis of physicians’ judgments of medical indications

Abstract: BackgroundThe aim of this study was to investigate whether physicians who felt strongly for or against a treatment, in this case a moderately life prolonging non-curative cancer treatment, differed in their estimation of medical indication for this treatment as compared to physicians who had no such sentiment. A further aim was to investigate how the notion of medical indication was conceptualised.MethodsA random sample of GPs, oncologists and pulmonologists (n = 646) comprised the study group. Respondents wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
0
11
0
2
Order By: Relevance
“…Still, it is the physician who makes the final decision regarding which treatment is offered. Physicians are not legally obligated to offer life-sustaining treatment for which they see no medical indication, even if this might be against the wishes of a well informed, competent patient [ 49 ]. In the case of NIV ineffectiveness, for instance, the physician would decide whether to offer IV or palliative symptom control.…”
Section: Comparing the Medical And Legal Framework For Existential Dmentioning
confidence: 99%
“…Still, it is the physician who makes the final decision regarding which treatment is offered. Physicians are not legally obligated to offer life-sustaining treatment for which they see no medical indication, even if this might be against the wishes of a well informed, competent patient [ 49 ]. In the case of NIV ineffectiveness, for instance, the physician would decide whether to offer IV or palliative symptom control.…”
Section: Comparing the Medical And Legal Framework For Existential Dmentioning
confidence: 99%
“…The judgement about whether or not there was a medical indication for a Caesarean in this situation may also have been influenced by the physicians’ values. Even though medical indications are traditionally considered as a purely medical matter, a study published in 2016 indicated that physicians’ personal values may influence how they interpret medical indications – a phenomenon called value‐impregnated factual judgements . Thirdly, the regional differences may have represented differences in competitive spirit with regard to which clinic can save the most premature newborn infants, with or without impairments.…”
mentioning
confidence: 99%
“…Die Bundesärztekammer bezeichnet die Indikation als ein "normatives Korrektiv", das dem Patientenwohl dient [9]. In der Literatur existieren unterschiedliche Verständnisse der Indikation [s. Beiträge in 6, 10, 15, 16], die teilweise neue Unterkategorien einführen [16], teilweise ausschließlich evidenzbasiert diskutieren [15]. Der Verlauf einer Entscheidungsfindung zwischen Arzt und Patient lässt sich folgendermaßen konzeptualisieren ▶Abb.…”
Section: Arbeitsschritt 1: Die Indikationsstellung Als Integraler Besunclassified
“…Es kann aber nicht davon abgesehen werden, dass in der Realität nicht nur professionsethische, sondern persönliche Wesenszüge und Haltungen des Arztes eine Rolle spielen. Etwa ein Viertel [36] bis ein Drittel [15] befragter Ärzte ließ nichtmedizinische "private values" in die Indikationsstellung einfließen. Darunter sind individuelle "private" Haltungen des Arztes (z.…”
Section: Diskussionunclassified